Biodelignification on Sengon (Paraserianthes falcataria) and Pine (Pinus merkusii) Using White-Rot Fungus Phanerochaete chrysosporium for the Development of Pulp and Paper Industries in Indonesia - Arief Widjaja; Dwina Moentamaria; Hanny F. Sangian (Journal of Fundamentals and Applications of Chemical Engineering, 2022)
Indonesia with its huge area of tropical forest is one of the biggest wood producing countries, thereby potential to become a big pulp and paper producing country. However, the present pulping/bleaching process uses chlorine that is very toxic to the environment. Biopulping process which reduce or eliminate the use of chlorine is therefore a very promising method. This research performs the biodelignification process using white-rot fungus Phanerochaete chrysosporium on Sengon (Paraserianthes falcataria) and Pine (Pinus merkusii) especially studies the effect of using different medium during incubation. Agar and okara were used for the base media in which the effect of important parameters such as mineral additive, buffering system and nitrogen content of the media were investigated. The highest degradation of lignin was 55% achieved on Sengon incubated for 30th days using buffered okara with nitrogen limited media. The research also shows that Sengon gives better results than Pine on the degree of its lignin degradation. The results also show that degradation of lignin always occurred together with the degradation of cellulose and hemmicellucose, although the degradation of the latter two materials is less than degradation of lignin. It was concluded from the experiment that more complete addition of nutrient with appropriate composition, appropriate adjustment of pH, water content, appropriate incubation time and temperature, would increase the degree of delignification and in the same time will decrease the degree of polisaccaride degradation.